Gully erosion in the Swan Hills, Alberta - St-Onge, Denis (Géographie physique et Quaternaire)

(untitled) (Les Presses de l’Université de Montréal, 1978)
Deforestation related to development work in the Swan Hills oilfield has resulted in gullying in road ditches, power lines and pipelines, right-of-ways and on well sites. The study of a large number of these gullies developed in clay and soft shale has made it possible to establish a nomograph to locate erosion control check dams. More importantly, the study suggests research avenues to determine the resistance of poorly consolidated material to erosion by running water.